LABORATORY INVESTIGATION ON PERFORMANCE OF CEMENT USING DIFFERENT ADDITIVE SCHEMES - REHMAN, KHALIL (2014)
The oil/gas well cement quality should be maintained during cementing job in order to prevent compressive strength retrogression. The previous research indicates that rheology and compressive strength of the cement slurry is affected by high temperature high pressure (HPHT) in the wellbore. So, in order to achieve the high early age compressive strength during the cementing job, different additives such as silica fame, dispersant and fluid loss control with different concentrations, i.e. silica fume % BWOC (15, 17, 19 and 21), dispersant Wt% (0.21, 0.26 and 0.31) and 1 Wt% fluid loss control were used to improve the performance ofthe cement slurry.